Modern approaches to interpretation of clinical trial results to evaluate the effectiveness of heart failure therapy. Analysis of the results of randomized trials PARADIGM-HF, DAPA-HF, EMPEROR-Reduced and VICTORIA - S. R. Gilyarevsky; Yu. V. Mareev (Российский кардиологический журнал)
The article discusses the results of modern studies evaluating the effectiveness of drug therapy for heart failure with reduced ejection fraction (HFrEF). Modern approaches to a comprehensive evaluation of data obtained in various randomized clinical trials (RCTs) are presented. The role of methods for presenting the RCT results is considered, as well as the difference between hazard ratio and relative risk is clarified. Expert opinions are discussed about the limitations of simplified approaches to comparing the results of large RCTs, which are based only on comparisons of hazard ratio without taking consideration of patient characteristics, study duration, and the absolute number of adverse outcomes that developed. Information is provided on the role of accounting for multiple comparisons in assessing clinical outcomes in RCTs. The article compares the VICTORIA results on the study of vericiguat in patients with a recent episode of HFrEF decompensation with RCTs on the evaluation of the effects of drugs that are part of standard therapy.